Synthesis of enantiomerically pure 2-(N-aryl, N-alkyl-aminomethyl)aziridines: a new class of ligands for highly enantioselective asymmetric synthesis. Issue 12 (15th December 2017) - Jarzyński, Szymon; Leśniak, Stanisław; Rachwalski, Michał
Graphical abstract: Abstract: A simple and effective synthesis of enantiomerically pure 2-( N -aryl-, N -alkyl-aminomethyl)aziridines from (2 S )- N -tritylaziridine-2-carboxylic acid methyl ester has been developed. Treating of this key ester with several primary and secondary amines in the presence of AlMe3 provided the corresponding chiral N -trityl-2-carboxamides, and their reduction performed with different reagents resulted in the formation of the expected 2-(aminomethyl)aziridines. The choice of reaction conditions allows to either keep or leave the trityl substituent in the product. Such 2-(aminoalkyl)aziridines have shown very high catalytic efficiency in the asymmetric arylation of aldehydes and in other testing asymmetric reactions. On the other hand, homochiral N -trityl-2-carboxamides are interesting building blocks for the synthesis of various biologically active compounds. Abstract : ( S )- N, N -Dimethyl-1-tritylaziridine-2-carboxamide: C24 H24 N2 O Ee = 99% [ α ]D  = −69.8 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-Pyrrolidin-1-yl(1-tritylaziridin-2-yl)methanone: C26 H26 N2 O Ee = 99% [ α ]D  = −74.5 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-Piperidin-1-yl(1-tritylaziridin-2-yl)methanone: C27 H28 N2 O Ee = 99% [ α ]D  = −55.5 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-Morpholino(1-tritylaziridin-2-yl)methanone: C26 H26 N2 O2 Ee = 99% [ α ]D  = −71.8 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -Benzyl-1-tritylaziridine-2-carboxamide: C29 H26 N2 O Ee = 99% [ α ]D  = −101.0 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -Phenyl-1-tritylaziridine-2-carboxamide: C29 H26 N2 O Ee = 99% [ α ]D  = −115.9 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -(4-Methoxyphenyl)-1-tritylaziridine-2-carboxamide: C29 H26 N2 O2 Ee = 99% [ α ]D  = −118.4 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -Mesityl-1-tritylaziridine-2-carboxamide: C31 H30 N2 O Ee = 99% [ α ]D  = −104.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( R )- N, N -Dimethyl-1-(1-tritylaziridin-2-yl)methanamine: C24 H26 N2 Ee = 99% [ α ]D  = −17.4 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-1-((1-Tritylaziridin-2-yl)methyl)pyrrolidine: C26 H28 N2 Ee = 99% [ α ]D  = −22.3 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-1-((1-Tritylaziridin-2-yl)methyl)piperidine: C27 H30 N2 Ee = 99% [ α ]D  = −19.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-4-((1-Tritylaziridin-2-yl)methyl)morpholine: C26 H28 N2 O Ee = 99% [ α ]D  = −20.5 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )- N -Benzyl-1-(1-tritylaziridin-2-yl)methanamine: C29 H28 N2 Ee = 99% [ α ]D  = −32.6 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )- N -((1-Tritylaziridin-2-yl)methyl)aniline: C28 H26 N2 Ee = 99% [ α ]D  = −41.3 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-4-Methoxy- N -((1-tritylaziridin-2-yl)methyl)aniline: C29 H28 N2 O Ee = 99% [ α ]D  = −45.8 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2, 4, 6-Trimethyl- N -((1-tritylaziridin-2-yl)methyl)aniline: C31 H32 N2 Ee = 99% [ α ]D  = −39.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( S )- N -(Aziridin-2-ylmethyl)aniline: C9 H12 N2 Ee = 99% [ α ]D  = +11.9 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -(Aziridin-2-ylmethyl)-4-methoxyaniline: C10 H14 N2 O Ee = 99% [ α ]D  = +14.0 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -(Aziridin-2-ylmethyl)-4-methoxyaniline: C12 H18 N2 Ee = 99% [ α ]D  = +12.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N, N -Dimethyl-1-tritylaziridine-2-carboxamide: C24 H24 N2 O Ee = 99% [ α ]D  = −69.8 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-Pyrrolidin-1-yl(1-tritylaziridin-2-yl)methanone: C26 H26 N2 O Ee = 99% [ α ]D  = −74.5 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-Piperidin-1-yl(1-tritylaziridin-2-yl)methanone: C27 H28 N2 O Ee = 99% [ α ]D  = −55.5 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )-Morpholino(1-tritylaziridin-2-yl)methanone: C26 H26 N2 O2 Ee = 99% [ α ]D  = −71.8 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -Benzyl-1-tritylaziridine-2-carboxamide: C29 H26 N2 O Ee = 99% [ α ]D  = −101.0 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -Phenyl-1-tritylaziridine-2-carboxamide: C29 H26 N2 O Ee = 99% [ α ]D  = −115.9 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -(4-Methoxyphenyl)-1-tritylaziridine-2-carboxamide: C29 H26 N2 O2 Ee = 99% [ α ]D  = −118.4 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -Mesityl-1-tritylaziridine-2-carboxamide: C31 H30 N2 O Ee = 99% [ α ]D  = −104.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( R )- N, N -Dimethyl-1-(1-tritylaziridin-2-yl)methanamine: C24 H26 N2 Ee = 99% [ α ]D  = −17.4 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-1-((1-Tritylaziridin-2-yl)methyl)pyrrolidine: C26 H28 N2 Ee = 99% [ α ]D  = −22.3 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-1-((1-Tritylaziridin-2-yl)methyl)piperidine: C27 H30 N2 Ee = 99% [ α ]D  = −19.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-4-((1-Tritylaziridin-2-yl)methyl)morpholine: C26 H28 N2 O Ee = 99% [ α ]D  = −20.5 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )- N -Benzyl-1-(1-tritylaziridin-2-yl)methanamine: C29 H28 N2 Ee = 99% [ α ]D  = −32.6 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )- N -((1-Tritylaziridin-2-yl)methyl)aniline: C28 H26 N2 Ee = 99% [ α ]D  = −41.3 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-4-Methoxy- N -((1-tritylaziridin-2-yl)methyl)aniline: C29 H28 N2 O Ee = 99% [ α ]D  = −45.8 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2, 4, 6-Trimethyl- N -((1-tritylaziridin-2-yl)methyl)aniline: C31 H32 N2 Ee = 99% [ α ]D  = −39.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( R ) Abstract : ( S )- N -(Aziridin-2-ylmethyl)aniline: C9 H12 N2 Ee = 99% [ α ]D  = +11.9 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -(Aziridin-2-ylmethyl)-4-methoxyaniline: C10 H14 N2 O Ee = 99% [ α ]D  = +14.0 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S ) Abstract : ( S )- N -(Aziridin-2-ylmethyl)-4-methoxyaniline: C12 H18 N2 Ee = 99% [ α ]D  = +12.7 ( c 0.3, CHCl3 ) Source of chirality: asymmetric synthesis Absolute configuration: ( S )